2010
DOI: 10.1007/s11060-010-0188-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of signal transducer and activator of transcription 3 (STAT3) in primary central nervous system diffuse large B-cell lymphoma: a retrospective analysis of 17 cases

Abstract: Most primary central nervous system lymphomas (PCNSL) occurring in immunocompetent patients are diffuse large B-cell lymphomas (DLBCL), characterized by poor prognosis. An activated B-cell (ABC) origin of PCNSL has been postulated based on bcl-6 and MUM-1 expression by majority of these tumors. ABC DLBCL has been functionally subdivided using gene expression profiling and immunohistochemical analysis into STAT3-high and STAT-3 low subsets. A potentially crucial difference between STAT3-high and STAT3-low ABC D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Therefore, the revised (2016) WHO Classification of Tumors of Hematopoietic and Lymphoid Tissues 29 recognizes extranodal DLBCL with specific anatomy as separate entities, such as intravascular large B-cell lymphoma, primary cutaneous DLBCL, primary cutaneous DLBCL-leg type, and primary DLBCL of the central nervous system (PCNSL), commonly representing an activated B-cell (ABC) phenotype. [30][31][32][33][34][35][36] Following this paradigm and because of their specific disease presentation and clinical behavior, we hypothesized that PB-DLBCL contains unique molecular characteristics. To address this theory, our study presents the first comprehensive GEP and targeted deep-sequencing analyses in a well-annotated and relatively large cohort of PB-DLBCL.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the revised (2016) WHO Classification of Tumors of Hematopoietic and Lymphoid Tissues 29 recognizes extranodal DLBCL with specific anatomy as separate entities, such as intravascular large B-cell lymphoma, primary cutaneous DLBCL, primary cutaneous DLBCL-leg type, and primary DLBCL of the central nervous system (PCNSL), commonly representing an activated B-cell (ABC) phenotype. [30][31][32][33][34][35][36] Following this paradigm and because of their specific disease presentation and clinical behavior, we hypothesized that PB-DLBCL contains unique molecular characteristics. To address this theory, our study presents the first comprehensive GEP and targeted deep-sequencing analyses in a well-annotated and relatively large cohort of PB-DLBCL.…”
Section: Introductionmentioning
confidence: 99%
“…A higher Stat3 activation in tumor cells is associated with lower survival rates of patients with several malignant tumors [ 14 17 ]. High levels of phosphorylated Stat3 (pStat3) protein were found in diffuse large B-cell lymphoma [ 18 , 19 ], while data on the expression of Stat3 in PCNSL are controversial [ 20 22 ]. Moreover, Stat3 favors proliferation and maintenance of CSCs, and its inhibition blocks tumor formation in glioblastoma [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Wang et al [26] found four cases of DLBCL with aberrant expression to CD 3, in one of the cases, the lymphoma occurred in the CNS in a 52-year-old woman; in the present study, expression of CD 3 was observed in a 47-year-old woman (Case 3) ( Figure 5); the biological significance and the mechanism for the CD 3 expression in DLBCL is not known; hence, we believe that other pan B markers such as CD 79ª, CD 138, PAX 5, and Mum-1 must be determined or molecular biology techniques must be implemented for the correct determination of the cell lineage of these unusual lymphomas. In the present series, three DLBCL in the SNC expressed Mum-1 and all expressed bcl-2 markers of bad prognosis; in a recent publication of 17 cases, expression of bcl2 and STAT-3 (Signal transducer and activator of transduction) was studied, emphasizing the low expression of this marker as a subtype of diffuse large B cell lymphoma originated from activated lymphocytes [27].…”
Section: Discussionmentioning
confidence: 70%
“…More than 460 expressed sequence tags were differentially expressed between PCNSL [27]. Regarding prognosis, several variables have been identified that affect survival negatively such as: age over 60 years, high serum levels of lactic dehydrogenase, hyperproteinorachia, and affectation of deep cerebral structures like periventricular regions, basal ganglia, brain stem, and cerebellum [28].…”
Section: Discussionmentioning
confidence: 99%